Non‐invasive imaging of cellulose microfibril orientation within plant cell walls by polarized Raman microspectroscopy. Issue 1 (18th September 2015) - Sun, Lan; Singh, Seema; Joo, Michael; Vega‐Sanchez, Miguel; Ronald, Pamela; Simmons, Blake A.; Adams, Paul; Auer, Manfred
ABSTRACT: Cellulose microfibrils represent the major scaffold of plant cell walls. Different packing and orientation of the microfibrils at the microscopic scale determines the macroscopic properties of cell walls and thus affect their functions with a profound effect on plant survival. We developed a polarized Raman microspectroscopic method to determine cellulose microfibril orientation within rice plant cell walls. Employing an array of point measurements as well as area imaging and subsequent Matlab‐assisted data processing, we were able to characterize the distribution of cellulose microfibril orientation in terms of director angle and anisotropy magnitude. Using this approach we detected differences between wild type rice plants and the rice brittle culm mutant, which shows a more disordered cellulose microfibril arrangement, and differences between different tissues of a wild type rice plant. This novel non‐invasive Raman imaging approach allows for quantitative assessment of cellulose fiber orientation in cell walls of herbaceous plants, an important advancement in cell wall characterization. Biotechnol. Bioeng. 2016;113: 82–90. © 2015 Wiley Periodicals, Inc. Abstract : The authors developed a noninvasive polarized Raman microspectroscopic method to determine distribution of cellulose microfibril orientation within rice plant cell walls. Clear differences in cellulose microfibril orientation were observed between different tissues of the wild type rice plant as well as between the wild type and the brittle culm mutant, a mutant compromised in secondary cell wall deposition. This is the first time that polarized Raman microspectroscopy was used to determine supramolecular organization in cell walls for herbaceous plants.